PENGARUH IRADIASI SINAR GAMMA TERHADAP PERTUMBUHAN VEGETATIF PADA DUA VARIETAS CABAI KERITING (Capsicum annum L.) - Nabila, Nailan; Penggalih, Paksi Mei; Retnyo Gumelar, Rima Margaretha; Huda, Amalia Nurul (Agros Journal of Agriculture Science, 2024)
Plant performance, growth response, and chili production from curly chili varieties currently need to be improved and adapted to changes in the agroecosystem and agroclimate which are changing as a result of climate change. One of the methods that can be used is using gamma-ray irradiation. This research aims to determine the growth response of chili plants resulting from gamma irradiation and determine the plant genotypes that has the best growth from the Iggo and Thunder progenitors. The research used 107 genotypes resulting from gamma mutation with 3 control varieties, namely Iggo, Thunder, and Tavirus with an Augmented RKLT Design with eight replications. The results showed that the growth in height and diameter of plants in curly chilies resulting from gamma-ray irradiation aged 2-14 WAP followed a sigmoid curve. The lag phase occurs at 2-4 WAP, the log phase occurs at 4-8 WAP and the stationary phase occurs at 8-14 WAP. Giving high doses of gamma irradiation to Iggo and Thunder chili seeds resulted in slower plant growth compared to treatments without irradiation or low doses in terms of plant height and plant diameter. Genotypes that have good growth are IG-1 17, IG-2 107, IG-2 108, IG-3 129, and IG-3 241 for Iggo offspring and genotypes TH-1 365, TH-1 366, TH-2 482, TH-2 488, TH-4 339, TH-4 340, TH-4 338, TH-4 367, TH-4 336, and TH-6 482 for the Thunder offspring.